FEATURES THAT INFLUENCE THE EXIT DECISION FROM THE PRIVATE PENSION SYSTEM IN TURKEY - KAYAM, Saime S.; CELİKTOPUZ, Merih; KORAY PARKIN, Mehmet (Journal of Advanced Studies in Finance; Vol 4 No 2 (2013): JASF Volume IV, Issue 2(8), Winter, 2013, 2013)
In Turkey, the Private Pension System was given a head start in 2003. Although the system aims to provide supplementary income to the public pensions at retirement, observations reveal that many participants prefer to exit the system before retirement. The purpose of this study is to identify the characteristics of participants, who are more likely to exit earlier than retirement using the total population of contract buyers since the start of the system until 2011. The data is obtained from the Pension Monitor Center, and covers the customer and contract characteristics of more than 75% of all lapse types in the period. Impact of demographic factors and contract features are examined using the logit model. We divide the sample into different groups of customers according to their monthly contributions to the system. The results of econometric analysis reveal evidence of a significant relationship between exit decision and features such as education level, occupation, total accumulated savings, geographical regions, pension sales channel and payment instruments. Staying long enough in the system increases participants’ continuity. Our elaborations also provide some tips for pension companies to ensure longevity and retirement of customers.